Exploring a South-South Dialogue: Spanish American Reception of Rabindranath Tagore - Bhattacharya, Nilanjana (Escuela de Lenguas Modernas, Universidad de Costa Rica, 2017)
This article concentrates on Rabindranath’s reception in a few Latin American countries. In the history of Latin America, early twentieth century was a crucial time when various Latin American countries were striving to come out of Europe’s grasp and establish an identity of their own. Yet, in the multifarious and multiracial society of Latin America it was difficult to define their ‘own’. At such a critical juncture of history, Rabindranath represented an alternative to various Latin American authors. He was, to them, a representative of a British colony who had been recognised and acknowledged by Europe, and thus symbolized a power/knowledge equivalent to that of Europe. This paper, divided in three parts, explores this reception and its impact, firstly by analyzing the history of the direct contact; then by focusing on the Latin American translations of Rabindranath’s works; and finally, by re-reading a few essays and critical-writings on Rabindranath. Among others, the paper alludes to Victoria Ocampo (1890-1979), the first and perhaps the only Latin American author who came in direct contact with Rabindranath; and some of the most important Nobel Laureates of Latin America, like Gabriela Mistral (1889-1957) and Pablo Neruda (1904-1973), to show how these authors and poets received Rabindranath in their own contexts.    Este artículo se concentra en la recepción de Rabindranath Tagore en algunos países de América Latina. En la historia de este continente, los primeros años del siglo XX fueron cruciales, porque muchos países de América Latina estaban esforzándose por destruir el control de Europa y establecer una identidad propia. Sin embargo, era difícil definir “lo propio” en una sociedad tan múltiple y multirracial. En un momento tan complejo de la historia, Tagore personificaba una alternativa para algunos autores de América Latina. Él era como un representante del “tercer mundo” que había ganado el reconocimiento de Europa, de los colonizadores; por tal motivo, su poder/sabiduría era tan fuerte como el de los británicos. Este artículo, dividido en tres partes, busca primero explorar la historia del contacto directo entre el poeta hindú y algunos escritores latinoamericanos; segundo, analizar varias traducciones de las obras de Tagore, hechas por latinoamericanos; y, finalmente, discutir unos ensayos y textos críticos realizados por estudiosos de América Latina sobre Tagore. El artículo se centra en Victoria Ocampo (1890-1979), la única autora del mundo hispano con quien Tagore tenía un contacto directo, y también en poetas de nombre mundial como Gabriela Mistral (1889-1957) y Pablo Neruda (1904-1973), para explicar cómo ellos recibieron a Tagore.